Minimally invasive approach to recurrent lumbar hernia secondary to nephrectomy. - Guerrero-Villota, Julieth Cristina (2022)
Introduction: lumbar hernia is a rare defect of the posterior abdominal wall, it represents between 1-2% of all abdominal hernias. Given its low frequency, only approximately 300 cases have been described in the literature since 1731. There is still not enough data to suggest a definitive repair method. The choice of the open or laparoscopic approach depends on the availability of resources and the experience of the surgeon. Objective: to present a clinical case of a secondary lumbar hernia managed by a minimally invasive approach. Materials and methods: review of the clinical history, presentation and images of a patient with a diagnosis of left lumbar hernia secondary to nephrostomy 6 years ago, description of the surgical technique, operative findings and outcomes. Review of the literature on lumbar hernias and their respective management. Results: 57-year-old woman with symptomatic left lumbar hernia secondary to nephrostomy 6 years ago. History of two interventions to correct the hernia without improvement. Correction was performed by laparoscopic approach, the transabdominal preperitoneal (TAPP) technique. Conclusions: Due to the low incidence of this pathology and the lack of collective experience, there is no standardized surgical method. A management alternative is the minimally invasive approach with widely known advantages such as: shorter hospital stay, lower consumption of analgesics and lower rate of absenteeism from work.